Host plants and Wolbachia shape the population genetics of sympatric herbivore populations. (12th September 2020) - Fu, Zhen; Meier, Amanda R.; Epstein, Brendan; Bergland, Alan O.; Castillo Carrillo, Carmen I.; Cooper, William R.; Cruzado, Regina K.; Horton, David R.; Jensen, Andrew S.; Kelley, Joanna L.; Rashed, Arash; Reitz, Stuart R.; et al.
Abstract: Changing climate and land‐use practices have the potential to bring previously isolated populations of pest insects into new sympatry. This heightens the need to better understand how differing patterns of host–plant association, and unique endosymbionts, serve to promote genetic isolation or integration. We addressed these factors in populations of potato psyllid, Bactericera cockerelli (Šulc), a generalist herbivore that vectors a bacterial pathogen ( Candidatus Liberibacter solanacearum, causal pathogen of zebra chip disease) of potato ( Solanum tuberosum L.). Genome‐wide SNP data revealed two major genetic clusters—psyllids collected from potato crops were genetically similar to psyllids found on a common weed, Lycium spp., but dissimilar from those found on another common non‐crop host, Solanum dulcamara L. Most psyllids found on Lycium spp. and potato represented a single mitochondrial cytochrome oxidase I (COI) haplotype that has been suggested to not be native to the region, and whose arrival may have been concurrent with zebra chip disease first emerging. The putatively introduced COI haplotype usually co‐occurred with endosymbiotic Wolbachia, while the putatively resident COI haplotype generally did not. Genetic intermediates between the two genetic populations of insects were rare, consistent with recent sympatry or reproductive isolation, although admixture patterns of apparent hybrids were consistent with introgression of genes from introduced into resident populations. Our results suggest that both host–plant associations and endosymbionts are shaping the population genetic structure of sympatric psyllid populations associated with different non‐crop hosts. It is of future interest to explicitly examine vectorial capacity of the two populations and their potential hybrids, as population structure and hybridization might alter regional vector capacity and disease outbreaks.